Preparation of PdxAuy bimetallic nanostructures with controllable morphologies supported on reduced graphene oxide nanosheets and wrapped in a polypyrrole layer. Issue 107 (15th October 2015) - Yao, Tongjie; Zuo, Quan; Wang, Hao; Wu, Jie; Zhang, Xiao; Sun, Jianmin; Cui, Tieyu
Abstract : A one-step method to prepare reduced graphene oxide/Pd x Au y /polypyrrole composites with good catalytic activity was introduced. The morphologies of alloy nanostructures could turn to be spherical, coral-like and porous cluster-like. Abstract : In this paper, we have introduced a one-step method to prepare Pd x Au y bimetallic nanostructures supported on reduced graphene oxide (rGO) nanosheets and wrapped in a polypyrrole (PPy) layer. By using a pyrrole monomer as a special reducing agent for metal salts, the morphologies of Pd x Au y bimetallic nanostructures could be easily turned to be spherical, coral-like and porous cluster-like via simply changing dosage or molar ratio of PdCl2 and HAuCl4 ·4H2 O. The roles of the pyrrole monomer and rGO support in formation of rGO/Pd x Au y /PPy composites were investigated in detail. Transmission electron microscopy, elemental mapping analysis, X-ray diffraction, X-ray photoelectron spectroscopy and Fourier-transform infrared spectra were used to characterize their morphologies, structures and compositions. Compared with corresponding rGO/Pd/PPy and rGO/Au/PPy composites, the as-prepared rGO/Pd x Au y /PPy composites displayed enhanced catalytic activity towards the reduction of 4-nitrophenol.